Are Politically Connected Firms More Likely to Evade Taxes? : Evidence from Tunisia - Rijkers, Bob (Published by Oxford University Press on behalf of the World Bank, 2019)
Are politically connected firms more likely to evade taxes? Using tax, social security, and customs records from Tunisia in which firms owned by former president Ben Ali and his family are identified, this paper demonstrates that connected firms were more likely to evade taxes. Ceteris paribus, connected firms are 4.6 percent more likely not to submit a tax declaration in spite of registering workers and/or customs transactions and 8.4 percent more likely to report anomalously low sales when submitting a tax declaration.